Market Entry by Divisionalized Firms: Where Experience Resides and When It Is Used - Aggarwal, Vikas A.; Chen, Mo; Wu, Brian (Organization Science, 2026)
Research on market entry shows that firms tend to grow by entering adjacent markets based on their prior experience. Much of this work implicitly treats knowledge embedded in the firm as uniformly available for strategic action. We argue instead that, in divisionalized firms, the effect of experience depends on where it resides across organizational units, which in turn shapes whether it becomes behaviorally relevant in evaluating entry opportunities. We posit that divisionalization, defined as a structural configuration in which a firm partitions activities into multiple operating units under a corporate umbrella, is associated with broader exposure to opportunities but weaker use of accumulated experience. Consequently, at the firm-level, divisionalization is associated with higher entry rates but a weaker relationship between firm-wide experience and entry. At the unit-level, entry is more strongly associated with experience located in the focal organizational unit than with experience residing in sister units. We further identify organizational conduits associated with the use of distributed experience, including recurring lateral interaction and integrative attention at the corporate center. We test our predictions using U.S. defense procurement following the September 11, 2001 attacks. Our findings show that within-firm organizational boundaries shape whether firms act on what they already know, shifting the study of market entry from experience accumulation to experience use.